2013
DOI: 10.1371/journal.pone.0084071
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Early Hepatic Stellate Cell Activation Reveals a Role for Igfbp3 in Cell Migration

Abstract: BackgroundScarring of the liver is the result of prolonged exposure to exogenous or endogenous stimuli. At the onset of fibrosis, quiescent hepatic stellate cells (HSCs) activate and transdifferentiate into matrix producing, myofibroblast-like cells. Aim and methodsTo identify key players during early HSC activation, gene expression profiling was performed on primary mouse HSCs cultured for 4, 16 and 64 hours. Since valproic acid (VPA) can partly inhibit HSC activation, we included VPA-treated cells in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 61 publications
3
39
0
Order By: Relevance
“…IGFBP3 and NTM were implicated in the maintenance of the qHSC phenotype. Consistent with previous observations, expression of IGFBP3 and NTM were strongly down‐regulated in alcohol‐activated hHSCs (vs. normal hHSCs). In turn, ADA2 , a growth factor for endothelial cells and a promoter of differentiation of M2 macrophages, was highly induced in ALD HSCs.…”
Section: Discussionsupporting
confidence: 92%
“…IGFBP3 and NTM were implicated in the maintenance of the qHSC phenotype. Consistent with previous observations, expression of IGFBP3 and NTM were strongly down‐regulated in alcohol‐activated hHSCs (vs. normal hHSCs). In turn, ADA2 , a growth factor for endothelial cells and a promoter of differentiation of M2 macrophages, was highly induced in ALD HSCs.…”
Section: Discussionsupporting
confidence: 92%
“…The mode of recruitment used in tissue regeneration is chemotaxis, which is directional migrationin response to a release of chemoattractants including GFs and chemokines (Vanden Berg‐Foels, ). Although IGFBP3 is reported to recruit endothelial precursor cells and hepatic stellate cells, the role of IGFBP3 on MSC homing is still unclear (Kielczewski et al, ; Mannaerts et al, ). In the present study, Transwell data suggested that exogenous IGFBP3 remarkably improved hBMSC migration in a dose‐dependent manner (Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that IGFBP-3 controls cell apoptosisand survival-related functions on cancer cells (Galluzzi et al, 2012;Johnson & Firth, 2014). In addition, IGFBP3 recruits a variety of resident cells toward injury sites, including hematopoietic stem cells/endothelial precursor cells and hepatic stellate cells (Chang et al, 2007;Kielczewski et al, 2009;Mannaerts et al, 2013). The role of IGFBP3 from hUCMSC-ECM on the recruitment of MSC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the insulin‐like growth factor I (IGF‐I) was able to induce senescence in HSCs. In vitro studies using primary rat HSCs (Mannaerts et al, ; Sumida et al, ) and the hepatic stellate lineage LX‐2 (Nishizawa et al, ) demonstrated the IGF‐I effects, inducing an increase in senescence markers (p21 and p53), and in the number of HSC positive to β‐galactosidase associated with senescence (SA‐β‐gal) (Handayaningsih et al, ). In addition, in vivo analysis emphasizes the role of IGF‐I in senescence and in the reversion of the hepatic fibrosing process.…”
Section: Hsc Senescence: Another Cellular Process That Helps To Contrmentioning
confidence: 99%